Agriculture Phenomena and Perspectives of Lebak Swamp in Jakabaring South Sumatra, Indonesia - Elisa Wildayana; M. Edi Armanto (Jurnal Ekonomi dan Studi Pembangunan, 2017)
The research aimed to analyze agriculture phenomena and perspectives of lebak swamp in Jakabaring South Sumatra Indonesia. The research used mix methods of quantitative and qualitative approaches. The description of the research area was assisted with interpretation of Landsat images in 1987 and 2015. The research resulted that farmer’s groups living in Jakabaring are divided into four group, namely indigenous people (people of Ogan, Komering, Musi, Enim, and Palembang), new comers (Javanese), spontaneous migration (Buginese, Banjarnese, Bataknese) and outside spontaneous migration (Chinese, Arabic). The total area of Jakabaring is approximately 5,525 ha, around 2,700 ha (48.87 %) was already landfilled by the Government in 1990, while the remaining 2,825 ha (51.13 %) is still not reclaimed. The landfill materials were directly sucked from mud, sand, silt and stones of the Musi River. Each lebak swamp typology shows specific soil characters, but after landfills all soils became homogenous because of uniform materials of landfills.  Patterns of land degradation after landfills are classified into three groups, namely making layers of water impermeability, changing vegetation types of land cover, and decreasing type and density of vegetation.Keywords: Agriculture, phenomena, perspectives, lebak, swampJEL Classification: O13, Q01